Implementasi Pemberdayaan Sosial Berbasis Keluarga Program Keluarga Harapan di Kec. Tigo Lurah, Sumatera Barat - Jafrianto Jafrianto; Jendrius Jendrius; Indraddin Indraddin (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This research was motivated by one of the objectives of PKH to create behavioral change and the independence of beneficiary families in accessing social education, health and welfare services. To achieve this change, PKH issued a program called the Family Development Session. Family Development Session is a community learning process to strengthen the increase in knowledge, public understanding of the importance of education, health and financial management for families so that they are free from poverty and can meet the needs of life independently. The purpose of this study is to describe the implementation and identify obstacles in the process of family-based social empowerment (Family Development session) in the district of Tigo Lurah. This study uses a qualitative approach with descriptive research type. Informants in this study were taken using a purposive sampling method. From the results of the study it was concluded that the family-based social empowerment (Family Development Session) of the Harapan family program in the Tigo Lurah sub-district was carried out through three stages, the first stage of awareness raising and behavior formation, the second stage of knowledge transformation, the third stage of capacity building. The obstacles of empowerment found in this research are that there is no good cooperation between the empowerment actors with the local government, no separate budget, lack of facilities and infrastructure and a lack of support from the leaders and the surrounding community.